1991
DOI: 10.2307/1941571
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Specific Weaning Success of Northern Elephant Seals in Relation to Previous Breeding Experience

Abstract: We studied the effect of age and previous breeding experience on the probability of successful reproduction in female northern elephant seals (Mirounga angustirostris). Reproductive data, collected over a 12—yr period, were analyzed by multiple logistic regression to describe the functional relationships among the variables. We also examined the relationships among age, experience, date of breeding, and reproductive success to determine if differences in timing explain age—specific productivity. Finally, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 19 publications
6
72
0
Order By: Relevance
“…This pattern is not consistent with a fecundity trade-off based on energy costs of reproduction, which the present study suggests would be most likely found in young individuals. This pattern is more consistent with an increase in weaning success with maternal experience in young animals that appears to plateau and then decline for very experienced females (Sydeman et al 1991). This increase in reproductive performance with experience may be an important selective force for high levels of expenditure in young females, despite potential fitness costs.…”
Section: Discussionsupporting
confidence: 55%
“…This pattern is not consistent with a fecundity trade-off based on energy costs of reproduction, which the present study suggests would be most likely found in young individuals. This pattern is more consistent with an increase in weaning success with maternal experience in young animals that appears to plateau and then decline for very experienced females (Sydeman et al 1991). This increase in reproductive performance with experience may be an important selective force for high levels of expenditure in young females, despite potential fitness costs.…”
Section: Discussionsupporting
confidence: 55%
“…In a broad range of species, first-time breeding females not only give birth to fewer offspring than experienced females, but the survival of their offspring is lower (e.g. Sydeman et al 1991;Daunt et al 2007). The increase in offspring survival for experienced females has mainly been attributed to improved experience in food provisioning (Daunt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for a higher juvenile mortality might be a greater predation risk because young animals are often less experienced and less able to escape, or they may be more sensitive to diseases or parasite infections. The decrease in survival probability with age (senescence) might arise from increased tooth wear (Gaillard et al, 1993), from cumulative effects of reproductive activities (Sydeman et al, 1991) or from deleterious mutations that have their effects later in life (Rose, 1991). Survival rates are typically different for the sexes if males have different life cycles than females.…”
Section: Introductionmentioning
confidence: 99%